Bioethanol production from sago pith waste using microwave hydrothermal hydrolysis accelerated by carbon dioxide - Thangavelu, S.K.; Abu Saleh, Ahmed; Ani, F.N. (Elsevier Ltd., 2014)
Bioethanol production from sago pith waste (SPW) using microwave hydrothermal hydrolysis accelerated by carbon dioxide was studied. The structural change in the SPW after hydrolysis, ethanol purity after fermentation, and distillation were investigated. Energy consumption for microwave hydrothermal hydrolysis was evaluated. A maximum of 43.8% theoretical glucose and 40.5% theoretical ethanol yield were obtained. The ethanol yield coefficient obtained in fermentation was 0.47 (g ethanol per g glucose) which was 15.6 g ethanol per 100 g dry SPW. It was also discovered that the lowest energy consumption occurred when energy input was fixed at 108 kJ (900W for 2 min), amounting to 33 kJ and 69 kJ to produce one gram glucose after hydrothermal hydrolysis and one gram ethanol after fermentation, respectively. The developed technique for SPW resulted in higher energy saving compared to previous techniques in the absence of enzymes, acid or base catalyst